Відповідь:
-1/3
Пояснення:
(7x^2-3) / (7x+4) = x-1 -- домножуємо обидві частини рівняння на 7x+4.
Отримаємо:
(7x^2-3) = (x-1) * (7x+4)
Розкриваємо дужки:
7x^2-3 = 7x^2+4x-7x-4
7x^2-3 = 7x^2-3x-4 -- 7x^2 скорочуєтся
-3 = -3x-4
Переносимо в іншу сторону:
3x = 3-4
3x = -1
x = -1/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
-1/3
Пояснення:
(7x^2-3) / (7x+4) = x-1 -- домножуємо обидві частини рівняння на 7x+4.
Отримаємо:
(7x^2-3) = (x-1) * (7x+4)
Розкриваємо дужки:
7x^2-3 = 7x^2+4x-7x-4
7x^2-3 = 7x^2-3x-4 -- 7x^2 скорочуєтся
-3 = -3x-4
Переносимо в іншу сторону:
3x = 3-4
3x = -1
x = -1/3